Hank the Cowdog: The Case of the Swirling Liller Tornado - Book 25 - Erickson, John R. 1943-; Holmes, Gerald L. (Perryton, TX : Maverick Books, 2012)
Hank the Cowdog and his sidekick Drover find themselves confronting a huge storm in the middle of the night.
Keywords: Hank the Cowdog (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Ranch life -- Juvenile fiction -- West (U.S.); Tornadoes -- Juvenile fiction; Hank the Cowdog (Fictitious character) -- Fiction; Dogs -- Fiction; Ranch life -- Fiction -- West (U.S.); Tornadoes -- Fiction; West (U.S.) -- Juvenile fiction; West (U.S.) -- Fiction